2022
DOI: 10.1186/s12887-022-03475-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of preserved bowel and mesentery fixation in apple-peel intestinal atresia

Abstract: Objective This study explored the feasibility of mesoplasty with end-to-side anastomosis in the treatment of different apple-peel mesenteric defects with high jejunal atresia. Methods A retrospective analysis was performed on 42 premature infants admitted to the hospital between 2014 and 2021. Prenatal ultrasound scans revealed bowel dilatation. The patients experienced vomiting after birth and produced white or no meconium. Plain radiography showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Operative intervention for surgical repair of such complex anatomy entails resection and anastomosis with or without enteroplasty. Recently, Han et al ( 11 ) studied mesopexy after primary anastomosis by retrograde small bowel mesentery fixation starting from the ileocecal region and proceeding around the enlarged blind pouch and reported mortality of 3 cases only from 42 patients. The other option for apple-peel atresia treatment is performing temporary stoma, which is sometimes indicated in cases with questionable bowel viability, significant peritonitis, or caliber discrepancies between both ends.…”
Section: Discussionmentioning
confidence: 99%
“…Operative intervention for surgical repair of such complex anatomy entails resection and anastomosis with or without enteroplasty. Recently, Han et al ( 11 ) studied mesopexy after primary anastomosis by retrograde small bowel mesentery fixation starting from the ileocecal region and proceeding around the enlarged blind pouch and reported mortality of 3 cases only from 42 patients. The other option for apple-peel atresia treatment is performing temporary stoma, which is sometimes indicated in cases with questionable bowel viability, significant peritonitis, or caliber discrepancies between both ends.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the interruption of intestinal continuity makes the distal intestinal tract smaller because of long-term disuse atrophy, while the proximal intestinal tract expands passively due to obstruction. The diameter ratio of proximal and distal intestinal tubes reflects the size of distal intestinal tubes, and the distance from the anastomotic site to the ileocecal region represents the length of the distal slender bowels, all of which impair the efficiency of excretion ( 13 , 14 ). Many studies have shown that early feeding is beneficial for the recovery of gastrointestinal function.…”
Section: Discussionmentioning
confidence: 99%